Peningkatan Mutu Pelayanan Kesehatan Melalui Training Manner Tenaga Kesehatan RSUD Kardinah Kota Tegal - Wiyanti Wiyanti; Puput Dewi Anggraeni; Hana Yulinda Fitriyani (Lembaga Pengembangan Kinerja Dosen, 2024)
The success of a hospital in carrying out its functions is marked by the results of quality service. In order for this to be realized, a hospital should be managed professionally by competent human resources and the availability of supporting facilities and infrastructure. One of the factors that influences the success of a hospital is good service quality. Quality health services are health services that can satisfy every user of health services. Another problem faced by partners is negative views of nurses, such as being rude, unfriendly, or unprofessional, which still often appear in the community. When friendliness and attention are absent, a climate of discomfort and reluctance to interact is created, resulting in suboptimal service. Health service providers, in addition to having professional ethics, also need to have good